Introducing an In Situ Capping Strategy in Systems Biocatalysis To Access 6‐Aminohexanoic acid1. Issue 51 (3rd November 2014) - Sattler, Johann H.; Fuchs, Michael; Mutti, Francesco G.; Grischek, Barbara; Engel, Philip; Pfeffer, Jan; Woodley, John M.; Kroutil, Wolfgang
Abstract The combination of two cofactor self‐sufficient biocatalytic cascade modules allowed the successful transformation of cyclohexanol into the nylon‐6 monomer 6‐aminohexanoic acid at the expense of only oxygen and ammonia. A hitherto unprecedented carboxylic acid capping strategy was introduced to minimize the formation of the dead‐end intermediate 6‐hydroxyhexanoic acid. For this purpose, the precursor ε‐caprolactone was converted in aqueous medium in the presence of methanol into the corresponding methyl ester instead of the acid. Hence, it was shown for the first time that esterases—specifically horse liver esterase—can perform the selective ring‐opening of ε‐caprolactone with a clear preference for methanol over water as the nucleophile.